Impact of a pharmacist-prepared interim residential care medication administration chart on gaps in continuity of medication management after discharge from hospital to residential care: a prospective pre- and post-intervention study (MedGap Study). Issue 3 (25th May 2012) - Elliott, Rohan A; Tran, Tim; Taylor, Simone E; Harvey, Penelope A; Belfrage, Mary K; Jennings, Rhonda J; Marriott, Jennifer L
Abstract : Objectives: To test the impact of a hospital pharmacist-prepared interim residential care medication administration chart (IRCMAC) on medication administration errors and use of locum medical services after discharge from hospital to residential care. Design: Prospective pre-intervention and post-intervention study. Setting: One major acute care hospital and one subacute aged-care hospital; 128 residential care facilities (RCF) in Victoria, Australia. Participants: 428 patients (median age 84 years, IQR 79–88) discharged to a RCF from an inpatient ward over two 12-week periods. Intervention: Seven-day IRCMAC auto-populated with patient and medication data from the hospitals' pharmacy dispensing software, completed and signed by a hospital pharmacist and sent with the patient to the RCF. Primary and secondary outcome measures: Primary end points were the proportion of patients with one or more missed or significantly delayed (>50% of prescribed dose interval) medication doses, and the proportion of patients whose RCF medication chart was written by a locum doctor, in the 24 h after discharge. Secondary end points included RCF staff and general practitioners' opinions about the IRCMAC. Results: The number of patients who experienced one or more missed or delayed doses fell from 37/202 (18.3%) to 6/226 (2.7%) (difference in percentages 15.6%, 95% CI 9.5% to 21.9%, p<0.001). The number of patients whose RCF medication chart was written by a locum doctor fell from 66/202 (32.7%) to 25/226 (11.1%) (difference in percentages 21.6%, 95% CI 13.5% to 29.7%, p<0.001). For 189/226 (83.6%) discharges, RCF staff reported that the IRCMAC improved continuity of care; 31/35 (88.6%) general practitioners said that the IRCMAC reduced the urgency for them to attend the RCF and 35/35 (100%) said that IRCMACs should be provided for all patients discharged to a RCF. Conclusions: A hospital pharmacist-prepared IRCMAC significantly reduced medication errors and use of locum medical services after discharge from hospital to residential care.